Big hero 6 [videorecording (DVD)] - Rouleau, Duncan; Seagle, Steven T.; Man of Action (Walt Disney Studios, 2015)
Robotics prodigy Hiro Hamada learns to harness his genius, thanks to his brilliant brother Tadashi and their like-minded friends: adrenaline junkie Go Go Tamago, neatnik Wasabi, chemistry whiz Honey Lemon, and fanboy Fred. When a devastating turn of events catapults them into the midst of a dangerous plot unfolding in the streets of San Fransokyo, Hiro turns to his closest companion - a robot named Baymax - and transforms the group into a band of high-tech heroes determined to solve the mystery.